Nanomodified Switch Induced Precise and Moderate Activation of CAR‐T Cells for Solid Tumors. Issue 12 (8th February 2023) - Wang, Xinyue; Meng, Fanyan; Li, Xiang; Xue, Luxin; Chen, Anni; Qiu, Yuling; Zhang, Zhifan; Li, Lin; Liu, Fengcen; Li, Yishan; Sun, Zhichen; Chu, Yanhong; et al.
Abstract: Chimeric antigen receptor (CAR)‐T cell therapy is a transformative treatment against advanced malignancies. Unfortunately, once administrated in vivo, CAR‐T cells become out of artificial control, and fierce response to CAR‐T therapy may cause severe adverse events, represented by cytokine‐release syndrome and on‐target/off‐tumor effects. Here, a nanomodified switch strategy is developed, leading to sustained and precise "on‐tumor only" activation of CAR‐T cells. Here, original gelatinase‐responsive nanoparticles (NPs) are used to selectively deliver the heterodimerizing switch, which is the key component of switchable CAR with separated activation modules. The "NanoSwitch" is tumor‐specific, thus inactivated switchable CAR‐T cells do little harm to normal cells, even if the normal cells express the target of CAR‐T. Owing to the sustained‐release effect of NPs, the CAR‐T cells are activated smoothly, avoiding sudden release of cytokine. These data introduce NanoSwitch as a universal and applicable solution to safety problems of CAR‐T therapy regardless of the target. Abstract : Here, nanoparticles based on gelatinase‐responsive strategy are used to construct "NanoSwitch" to control the activation process of chimeric antigen receptor (CAR)‐T cells, leading to on‐site activation of CAR‐T cells at the tumor region in a precise and sustainable way. This platform has promising potential to prevent the main obstacles in the CAR‐T therapy for solid tumors including cytokine‐release syndrome and on‐target/off‐tumor toxicity.